Prognostic value of nitric oxide in pediatric septic shock - Ari L. Runtunuwu; Jeanette I. Ch. Manoppo; Dasril Daud; Irawan Yusuf; Idham Jaya Ganda (Indonesian Pediatric Society, 2016)
Background Nitric oxide (NO) play a key role in the pathogenesis of septic shock. Nitrit oxide metabolite is reported as a good predictor for shock although its role as mortality predictor in sepsis still controversial.Objective To assess the serum nitric oxide (NO) levels and outcomes in pediatric patients with septic shock.Methods We conducted a prospective cohort study from January 2013 to April 2014 in Pediatric Intensive Care Unit (PICU) Prof. Dr. R. D. Kandou Hospital, Manado. Subjects were patients agedÂ 1 month-12 years diagnosed with septic shock. We measured initial serum NO and observed its outcomes in all subjects.Results A total of 37 patients with septic shock met the study criteria. Nineteen children were male (51.4%). Seventeen subjects died and 20 subjects survived. The mean age of subjects with septic shock was 37.3 (SD 14.2) months. The mean serum NO level was significantly higher in the group who died [33.2 Î¼M; 95% CI 23.6 to 42.7] than in the group who survived [13.8 Î¼M; 95%CI 11.6 to 15.9] (P<0.01). The serum NO cut-off point for predicting mortality was 16.15 ÂµM. For NO levels of more than 16.15 ÂµM, the positive predictive value was 72.2% and negative predictive value was 78.9% (OR 9.750; 95%CI 2.154 to 44.138).Conclusion In pediatric patients with septic shock, serum NO levels are significantly higher in those who died than in those who survived. Serum nitric oxide level can be used to predict outcomes of patients with septic shock.